Investigation of road accidents on Lithuanian state roads - Sadauskas, Vigilijus (Transport, 2006)
Fast development of the number of vehicles is closely related to large benefit for the public and also to certain undesirable large numbers of injured and killed people involved in the accidents. What must be done? It is necessary in the nearest future to improve traffic safety situation in Lithuania. This can be reached after the detailed evaluation of accident analysis and investigations. Only a systematic and consistent approach to comprehensive traffic accident analysis can reduce the losses of lives and property in road traffic. This approach can be summarized in basic action – to establish the accident analysis and investigation groups.First Published Online: 27 Oct 2010